МЕТОДИКА ФОРМУВАННЯ ХУДОЖНЬО-ВИКОНАВСЬКОЇ МАЙСТЕРНОСТІ МАЙБУТНІХ ПІАНІСТІВ З КНР - Сянюн, Чжан (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті висвітлюється методика формування художньо-виконавської майстерності майбутніх піаністів з КНР. У даному контексті автор розглядає наступні педагогічні умови: усвідомлення суб’єктами освітнього процесу сутності та цінності художньо-виконавської майстерності для професійного розвитку; організація художньо-виконавської діяльності майбутніх піаністів з КНР на основі задачної технології; стимулювання рефлексивно-творчої діяльності піаніста в музично-виконавському процесі. Особлива увага приділена етапам, основним положенням, формам та методам, якими керувались при виборі педагогічних умов. В статье освещается методика формирования художественно-исполнительского мастерства будущих пианистов из КНР. В данном контексте автор рассматривает следующие педагогические условия: осознание субъектами образовательного процесса сущности и ценности художественно-исполнительского мастерства для профессионального развития; организация художественно-исполнительской деятельности будущих пианистов из КНР на основе задачной технологии; стимулирование рефлексивно-творческой деятельности пианиста в музыкально-исполнительском процессе. Особое внимание уделено этапам, основным положениям, формам и методам, которыми руководствовались при выборе педагогических условий. In the article the method of implementation and features in the professional training of future pianists from China pedagogical conditions of formation of artistic and performance skills, understanding educational process subjects the nature and value of artistic and performance skills for professional development; organization of artistic and performance of future pianists from people’s republic of china(PRC) of task-based technologies; stimulate reflexive and creative activities pianist performing in the musical process. The author examines the stages, the basic provisions, forms and methods that are guided in choosing the educational environment. Among them: the course «Fundamentals formation of artistic and performance skills» workshop «Creative Workshop» reflective conversation; visits and analysis of concert performances of their peers and professional musicians; familiarization with best examples of artistic and performance skills; analysis of their own performance and training and so on.